Asymmetric consequences of host plant occupation on the competition between the whiteflies Bemisia tabaci cryptic species MEAM1 and Trialeurodes vaporariorum (Hemiptera: Aleyrodidae). Issue 12 (26th February 2014) - Zhang, Gui‐Fen; Lövei, Gábor L; Hu, Man; Wan, Fang‐Hao
Abstract BACKGROUND The two common whitefly species, Bemisia tabaci (Gennadius) MEAM1 and Trialeurodes vaporariorum (Westwood), often co‐occur on their host plants. The effect of host plant occupation by one species on later‐arriving conspecific individuals or on the other competing species was examined. RESULTS Resource preoccupied by T. vaporariorum had mostly negative effects on the life history parameters of later‐arriving conspecifics. Red‐eyed nymph and immature survival of T. vaporariorum decreased when resource was preoccupied by conspecifics, irrespective of the previous occupation scenario. However, resource preoccupied by T. vaporariorum had only minor detrimental effects on the performance of later‐arriving B. tabaci MEAM1. In the opposite colonisation sequence, previous occupation by B. tabaci MEAM1 had no significant effects on the life history parameters of later‐arriving conspecifics, but severe detrimental effects were observed on the performance of later‐arriving T. vaporariorum. Total immature survival of T. vaporariorum decreased in both weak and strong previous occupation situations by B. tabaci MEAM1. CONCLUSION The interspecific interactions between B. tabaci MEAM1 and T. vaporariorum were asymmetric, with B. tabaci MEAM1 being the superior competitor. This superiority could partially explain the rapid spread of B. tabaci MEAM1 in China. © 2013 Society of Chemical Industry